Pengaruh Kemasan, Kondisi Ruang Simpan dan Periode Simpan terhadap Viabilitas Benih Caisin Brassica chinensis L.) - Rahayu, Esti; Widajati, Eny (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
The objective of this trial was to determine the effect of the best  packaging material, storage room condition and storage period for the seed viability of caisin. The trial was conducted at the seed laboratory of the Department of Agronomy and Horticulture, Faculty of Agriculture, Bogor Agriculture University in March- October 2005. The experiment was arranged in completely randomized design with three factors. The first factor was packaging materials (paper, polyethylene and aluminum foil); the second factor was storage room conditions (ambient room, Air Conditioned (AC) room and refrigerator); the third factor was storage periods (0, 3, 6, 9, 12 and 15 weeks). The result of this research showed that packaging materials gave significant effect on the dry weight of normal seedling. Storage periods gave very significant effect on germination percentage, dry weight of normal seedling, maximum growth capacity, and vigor index. The interaction between packaging materials, storage room conditions and storage periods gave very significant efflect on germination rate. Based on the dry weight of normal seedling, polyethylene and aluminum foil package gave the same result, on the other hand paper package gave the lowest dry weight of normal seedling than that aluminum foil package.  Based on the germination percentage, dry weight of normal seedling, maximum growth capacity, and vigor index the seed viability of caisin did not  decrease, even after 15 weeks of storage period.   Key words : Packaging materials, storage periods and seed viability